Padma Flower Ornaments on the Gedhe Kauman Mosque in Yogyakarta and Its Transformation - Wiyono, Erina; Damayanti, Nuning Yanti; Destiarmand, Achmad Haldani; Sunarya, Yan Yan (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2025)
The pride in the identity of a nation which is associated with the long history can be transformed into a valuable asset for both the present and the future. This can be achieved through the development of cultural heritage in the form of the artifacts owned. The diverse traditions associated with past legacies establish an inseparable connection between Indonesia and cultural history. An example of cultural heritage are the buildings that serve as evidence of the activities conducted in the past. Moreover, the influence of cultural, religious, and social systems caused by acculturation is evident in different forms of mosque buildings in Indonesia, specifically on Java Island. This can be observed from the adoption of ornaments in the Western period, starting from the 16th century. An example was the adoption of Padma Flower also known as the Lotus and Red Lotus by mosque buildings during the early introduction of Islam. The flower is also found in the house of worship, the Gedhe Kauman Mosque in Yogyakarta, built in 1773 AD by Sri Sultan Hamengku Buwono 1. Therefore, this research aimed to explain (1) the form of Padma Flower ornaments based on the shape, and (2) the changes in the form with subsequent influence on the present design. A qualitative method with a Visual Adaptation strategy was used to describe and analyze the form of the flower to determine the formulation process. The adaptation of Padma Flower ornaments in different places was expected to assist the process of using motif as a reference in the field of art and design.